(untitled) (Palestine Issues on Indonesian Society, 2025)
This paper examines how Palestinian issues are incorporated into Indonesian educational discourse, particularly in relation to political history and moral education. The study analyzes textbooks, curricula, and classroom discussions on Palestine in Indonesian schools, focusing on how educators frame the Palestinian struggle as part of global history and Islamic moral teachings. By studying the role of Palestinian solidarity in educational settings, the paper investigates how Palestinian issues are presented to students within the context of Indonesian foreign policy, religious values, and national identity. It explores the impact of these educational practices on Indonesian youth’s understanding of Palestine, political conflicts, and global justice. The research shows that while Palestinian issues are often framed in terms of Islamic solidarity, there is also a broader moral discourse on justice, human rights, and anti-colonial resistance. This paper argues that the Palestinian cause, while politically charged, is predominantly treated as a moral issue in Indonesian education, with implications for shaping future generations’ attitudes toward global politics and human rights.